Effect of dietary probiotic supplementation on carcass traits and haematological responses of broiler chickens fed shea butter cake based diets - Paschal Chukwudi Aguihe; Abiodun Solomon Kehinde; Sufiyan Abdulmumini; Iván Camilo Ospina-Rojas; Alice Eiko Murakami (Acta Scientiarum. Animal Sciences, 2017)
A 42-day study was conducted to investigate probiotic supplementation on shea butter cake (SBC) based diets of broilers on the carcass traits and haematological indices. A total of 280, 1-day old Arbor acres strain broiler chicks were divided into 7 dietary treatments with 4 replicates of 10 birds each in a completely randomized design. Diet 1 (control diet) has no SBC and probiotic supplementation while remaining 6 diets contained 5, 10, and 15% levels of SBC each with (+) or without (-) probiotic supplementation. The results showed that carcass parameters and prime cuts weights increased (p < 0.05) in birds fed probiotic-SBC diets compared to control diets. Abdominal fat content was lower (p < 0.05) in birds fed probiotic-SBC diets than those on control and non-probiotic SBC diets. Differences in relative organ weights among all treatments were non-significant (p > 0.05) except for liver and bursa weight. Packed cell volume and hemoglobin contents were higher (p < 0.05) in birds fed probiotic-SBC diets than the group without probiotic supplementation compared to those on control diet. In conclusion, supplementation of multi-strain probiotic improved carcass traits, prime cut-parts and relative organ weights without any adverse effect on the blood parameters up to 15% inclusion level.